Construal‐Level Effects on Preference Stability, Preference‐Behavior Correspondence, and the Suppression of Competing Brands - Kardes, Frank R.; Cronley, Maria L.; Kim, John (Journal of Consumer Psychology, 2006)
Construal level theory (Trope & Liberman, 2003) suggests that construal level––or the degree of abstractness of mental representations––increases with temporal, spatial, or sensory distance. Three experiments show that the mere presence of a set of target brands at the time a choice is made encourages consumers to represent the brands in memory in terms of concrete lower‐level construals. Consequently, preference stability is higher, preference‐behavior consistency is greater, and product category‐identification latencies for competing brands are slower. Furthermore, the mere presence of target brands at the time of choice affects preference‐behavior consistency independent of the effects of direct experience. Implications for an understanding of spontaneous preference formation, preference representation, and preference elicitation are discussed.